Prevalensi Indikasi Perawatan Tumpatan pada Pasien yang Berkunjung ke RSGM Universitas Jember Tahun 2015 (The Indication Prevalence of Restoration Treatments in Patients Who Attended Dental Hospital University of Jember in 2015) - Ilonavia Satiti; Dwi Warna Aju Fatmawati; Sri Lestari (Pustaka Kesehatan, 2017)
Introduction:Teeth are hard tissue that serve as the process of mastication in humans. In the event of tooth damages, they can not perform their functions optimally. Dental hard tissue damages include caries, attrition, abrasion, erosion and fracture.The damage of tooth hard tissues can change the anatomical shape of the tooth which make them fail to function properly. Restoring the damaged anatomical shape can be achieved by restoration or fillings.Objective: To know the indication of restoration treatments in patients who attended RSGM University of Jember in 2015.Methods:This research was a descriptive study with Cross Sectional Study approach. The study was conducted at RSGM University of Jember. The number of respondents were 100 which was obtained by using the Slovin formula.Result and Conclusion: The prevalence of restoration treatments indication in patient who attended RSGM University of Jember in 2015 was 89% . It was distributed based on sex was 52,8% for women and 47,2% for men, based on age groups, 21-26 year-old-group had the highest prevalence, while 33-44 year-old-group had the lowest prevalence.  Keywords: restoration treatments, prevalence